2009
DOI: 10.1158/0008-5472.can-08-2603
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Peptidyl-Prolyl-Isomerase Pin1 Enhances the Responses of Acute Myeloid Leukemia Cells to Retinoic Acid via Stabilization of RARα and PML-RARα

Abstract: The peptidyl-prolyl-isomerase Pin1 interacts with phosphorylated proteins, altering their conformation. The retinoic acid receptor RARA and the acute-promyelocytic-leukemia-specific counterpart PML-RARA directly interact with Pin1. Overexpression of Pin1 inhibits ligand-dependent activation of RARA and PML-RARA. Inhibition is relieved by Pin1-targeted short interfering RNAs and by pharmacologic inhibition of the catalytic activity of the protein. Mutants of Pin1 catalytically inactive or defective for client-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 51 publications
(46 reference statements)
1
52
0
Order By: Relevance
“…In fact, anti-cancer agents such as methotrexate and azathioprine are used for the treatment of RA (48). Pin1 inhibition has anti-cancer effects in experimental studies (49,50), and recently, diverse chemical-based or peptide-based Pin1 inhibitors have been synthesized (51,52). We found that multiple treaments of 10 mg/kg juglone caused severe toxic effects in mice, such as paralysis and even death (three among seven mice).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, anti-cancer agents such as methotrexate and azathioprine are used for the treatment of RA (48). Pin1 inhibition has anti-cancer effects in experimental studies (49,50), and recently, diverse chemical-based or peptide-based Pin1 inhibitors have been synthesized (51,52). We found that multiple treaments of 10 mg/kg juglone caused severe toxic effects in mice, such as paralysis and even death (three among seven mice).…”
Section: Discussionmentioning
confidence: 90%
“…23) cells, RARa À/À mouse embryo fibroblasts (MEF) 20 and freshly isolated AML blasts from the peripheral blood of four AML patients (Supplementary Table I) were cultured as described. 23 All patients gave informed consent for sample collection. The protocol for the collection of leukemic blasts from AML patients was approved by the local ethical committee.…”
Section: Nb4mentioning
confidence: 99%
“…NBT-reducing activity was measured and values are the mean ± s. Pull-down, immunoprecipitation and far-Western experiments were as described. 23 For the pull-down experiments, 23 we used GST-p38a and GSTDNp38a. For the immunoprecipitation experiments in NB4 cells, anti-RARa antibodies 23 were used.…”
Section: Nb4mentioning
confidence: 99%
See 2 more Smart Citations